Positive electrode active material, method of preparing same, and positive electrode and rechargeable lithium battery including same

By forming a double coating of Al and Co on the surface of the lithium nickel-manganese composite oxide positive electrode active material, the problem of shortage of cobalt supply in the positive electrode active material of lithium battery is solved, and the effect of high capacity, long cycle life and improving high voltage and high temperature characteristics is achieved.

CN119517952APending Publication Date: 2025-02-25SAMSUNG SDI CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411173059.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-24
Filing Date
2024-08-26
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The active substances of existing lithium batteries contain rare metal cobalt, which is short of supply and high cost, making it difficult to meet the needs of high energy density and long cycle life.

Method used

Laminated lithium nickel-manganese composite oxides were used as positive electrode active substances, and a double coating of Al and Co was formed on its surface, and prepared by heat treatment and wet coating.

Benefits of technology

It achieves high capacity, long cycle life and improves high voltage and high temperature characteristics, reduces gas generation and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119517952A_ABST
    Figure CN119517952A_ABST
Patent Text Reader

Abstract

The present application discloses a positive electrode active material, a method of preparing the same, and a positive electrode and a rechargeable lithium battery including the same. The positive electrode active material includes a core particle including a layered lithium nickel manganese-based composite oxide, a first coating layer on a surface of the core particle and containing Al, and a second coating layer on the first coating layer and containing Co.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Disclosed are a positive electrode active material, a preparation method thereof, a positive electrode including the same, and a rechargeable lithium battery. Background Art

[0002] Portable information devices (such as, for example, cellular phones, laptop computers, smart phones, etc.) and / or electric vehicles have used rechargeable lithium batteries with high energy density and easy portability as driving power sources. Recently, research has been actively conducted to use rechargeable lithium batteries with high energy density as driving power sources and / or energy storage power sources for hybrid vehicles and / or electric vehicles.

[0003] Various positive electrode active materials have been studied to realize rechargeable lithium batteries for the above-mentioned purposes. Among them, lithium nickel oxides, lithium nickel manganese cobalt composite oxides, lithium nickel cobalt aluminum composite oxides and lithium cobalt oxides are mainly used as positive electrode active materials. However, although the demand for rechargeable lithium batteries with large size, high capacity and / or high energy density has increased recently, the supply of positive electrode active materials containing rare metal cobalt is expected to be in serious shortage. For example, because cobalt is expensive and lacks remaining reserves, people are interested in developing positive electrode active materials that exclude cobalt or use cobalt in reduced amounts. Summary of the invention

[0004] Some embodiments of the present disclosure provide a positive electrode active material, which includes a layered lithium nickel manganese composite oxide, thereby ensuring economic feasibility, high capacity and long cycle life characteristics and showing improved high voltage characteristics and high temperature characteristics. Embodiments of the present disclosure provide a method for preparing a positive electrode active material, a positive electrode including the positive electrode active material, and a rechargeable lithium battery.

[0005] In some embodiments, the positive electrode active material includes: a core particle including a layered lithium nickel manganese-based composite oxide, a first coating layer on a surface of the core particle and containing Al, and a second coating layer on the first coating layer and containing Co.

[0006] In some embodiments, the method for preparing the aforementioned positive electrode active material includes: mixing a nickel manganese composite hydroxide and a lithium raw material together, and performing a first heat treatment to obtain a layered lithium nickel manganese composite oxide; adding an aluminum raw material to an aqueous solvent, followed by mixing, adding a layered lithium nickel manganese composite oxide, followed by mixing, and adding a Co raw material, followed by mixing; and drying them and performing a second heat treatment.

[0007] In some embodiments, the positive electrode includes a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector, wherein the positive electrode active material layer includes the aforementioned positive electrode active material.

[0008] In some embodiments, a rechargeable lithium battery includes the aforementioned positive electrode, negative electrode, and electrolyte.

[0009] The positive electrode active material according to some embodiments can maximize or increase the capacity while minimizing or reducing the production cost to ensure long cycle life characteristics and improve high voltage characteristics and high temperature characteristics. If the positive electrode active material is applied to a rechargeable lithium battery, a high initial charge / discharge capacity and efficiency can be achieved under high voltage operating conditions, a long cycle life characteristic can be achieved, and the amount of gas generated due to high voltage and high temperature operation can be effectively suppressed or reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] The accompanying drawings, together with the specification, illustrate embodiments of the presently disclosed subject matter, and together with the description, serve to explain principles of embodiments of the presently disclosed subject matter.

[0011] Figure 1 A cross-sectional perspective view is provided to illustrate a rechargeable lithium battery according to some embodiments.

[0012] Figure 2 A cross-sectional view illustrating a rechargeable lithium battery according to some embodiments.

[0013] Figure 3-Figure 4 A perspective view illustrating a rechargeable lithium battery according to some embodiments.

[0014] Figure 5 is a scanning electron microscope (SEM) image of a cross section of the positive electrode active material of Example 1.

[0015] Figure 6 To highlight the Figure 5 Image of the Al element in .

[0016] Figure 7 To highlight by SEM-EDS analysis Figure 5 Image of the Co element in .

[0017] <Description of Reference Numerals>

[0018] 100: Rechargeable lithium battery 10: Positive electrode

[0019] 11: Positive electrode lead lug 12: Positive electrode terminal

[0020] 20: Negative electrode 21: Negative electrode lead lug

[0021] 22: Negative electrode terminal 30: Separator

[0022] 40: electrode assembly 50: shell

[0023] 60: Sealing member 70: Electrode terminal piece

[0024] 71: Positive electrode terminal tab 72: Negative electrode terminal tab DETAILED DESCRIPTION

[0025] Hereinafter, example embodiments will be described in more detail so that those skilled in the art can easily implement them. However, the subject matter of the present disclosure may be implemented in many different forms and is not to be construed as limited to the example embodiments set forth herein.

[0026] The terms used herein are only used to describe the embodiments and are not intended to limit the present disclosure. Unless the context clearly indicates otherwise, a singular expression includes a plural expression.

[0027] As used herein, "combinations thereof" refers to mixtures, laminates, composites, copolymers, alloys, blends, reaction products, and the like, of the components.

[0028] In this document, it should be understood that terms such as "comprises", "includes" or "have" are intended to indicate the presence of the implemented features, quantities, steps, elements or combinations thereof, but it does not exclude the possibility of the presence or addition of one or more other features, quantities, steps, elements or combinations thereof.

[0029] In the drawings, the size (e.g., thickness) of layers, films, panels, regions, etc. may be exaggerated for clarity, and the same reference numerals represent the same elements throughout the specification. It will be understood that if an element (such as a layer, film, region, or substrate) is referred to as being "on" another element (such as a layer, film, region, or substrate), it may be directly on the other element (such as a layer, film, region, or substrate), or there may also be intervening elements. In an embodiment, if an element is referred to as being "directly on" another element (such as a layer, film, region, or substrate), there are no intervening elements.

[0030] In an embodiment, a “layer” herein includes not only a shape formed on the entire surface but also a shape formed on a partial surface if viewed from a plan view.

[0031] The average particle size can be measured by any suitable method commonly used in the art (e.g., by a particle size analyzer, and / or by a transmission electron microscope image and / or a scanning electron microscope image). In an embodiment, the average particle size value can be obtained by measuring using a dynamic light scattering method, performing data analysis, counting the number of particles in each particle size range, and calculating therefrom. Unless otherwise specified, the average particle size (D 50) may refer to the diameter of particles of which the cumulative volume is 50% by volume in a particle size distribution. As used herein, if no other definition is provided, the average particle diameter (D 50 ) means the diameter of particles accounting for 50% by volume of the cumulative volume in a particle size distribution obtained by randomly measuring the sizes (diameters or major axis lengths) of about 20 particles in a scanning electron microscope image.

[0032] In this document, "or" is not interpreted as an exclusive meaning. For example, "A or B" is interpreted to include A, B, A+B, etc.

[0033] As used herein, the term "metal" should be interpreted as a concept including common metals, transition metals, and metalloids (semimetals).

[0034] Positive electrode active material

[0035] In some embodiments, the positive electrode active material includes: a core particle including a layered lithium nickel manganese composite oxide (hereinafter, referred to as "lithium nickel manganese composite oxide"), a first coating layer on the surface of the core particle containing Al, and a second coating layer on the first coating layer containing Co.

[0036] Since the price of rare metal cobalt has risen sharply recently, there is interest in developing positive electrode active materials that exclude cobalt or reduce the cobalt content. Among them, positive electrode active materials with olivine crystal structure (such as lithium iron phosphate (LFP), lithium manganese phosphate (LMP), lithium manganese iron phosphate (LMFP), etc.) and / or positive electrode active materials with spinel crystal structure (such as lithium manganese oxide (LMO), etc.) are limited in achieving high capacity due to the small amount of lithium available in the structure. Due to the high amount of available lithium in the structure, the layered lithium nickel manganese positive electrode active material has excellent capacity and efficiency characteristics, making it suitable as a material for high-capacity batteries. However, as cobalt, which plays a key role in the layered structure, is removed, the structural stability is reduced, the impedance (e.g., resistance) increases, and it becomes difficult to ensure long cycle life characteristics. The layered lithium nickel manganese positive electrode active material without cobalt may have the problem of accelerating side reactions with the electrolyte under high voltage and high temperature conditions, resulting in increased gas generation and deterioration of cycle life characteristics.

[0037] In some embodiments, a first coating layer and a second coating layer are introduced on the surface of the core particles of the layered lithium nickel manganese-based composite oxide to provide a positive electrode active material that can maximize or increase capacity and efficiency and achieve long cycle life characteristics by reducing gas generation even under high voltage and / or high temperature conditions.

[0038] Nuclear particles

[0039] The core particles include a lithium nickel manganese-based composite oxide.

[0040] Based on 100 mol% of the total metals other than lithium in the lithium nickel manganese composite oxide, the nickel content may be greater than or equal to about 60 mol%, for example, about 60 mol% to about 80 mol%, about 65 mol% to about 80 mol%, about 70 mol% to about 80 mol%, about 60 mol% to about 79 mol%, about 60 mol% to about 78 mol%, or about 60 mol% to about 75 mol%. If the nickel content meets the above range, high capacity can be achieved and structural stability can be increased even if the cobalt content is reduced.

[0041] For example, based on 100 mol% of the total metals other than lithium in the lithium nickel manganese composite oxide, the manganese content may be greater than or equal to about 10 mol%, for example, about 10 mol% to about 40 mol%, for example, about 15 mol% to about 40 mol%, about 15 mol% to about 35 mol%, about 15 mol% to about 30 mol%, or about 20 mol% to about 30 mol%. If the manganese content satisfies the above range, the positive electrode active material can improve structural stability while achieving high capacity.

[0042] The lithium nickel manganese composite oxide may be, for example, a lithium nickel manganese aluminum composite oxide further including aluminum in addition to nickel and manganese. If the lithium nickel manganese composite oxide includes aluminum, it maintains a stable layered structure even if the cobalt element is excluded from the structure. The aluminum content of the lithium nickel manganese composite oxide based on 100 mol% may be greater than or equal to about 0.1 mol%, greater than or equal to about 0.5 mol%, or greater than or equal to about 1 mol%, for example, about 1 mol% to about 3 mol%, about 1 mol% to about 2.5 mol%, about 1 mol% to about 2 mol%, or about 1 mol% to about 2.5 mol%. If the aluminum content meets the above range, even if cobalt is excluded, a stable layered structure can be maintained, the problem of structural collapse caused by charging and discharging can be suppressed or reduced, and the long cycle life characteristics of the positive electrode active material can be achieved.

[0043] According to some embodiments, the concentration of aluminum in the core particle may be uniform (or substantially uniform). In an embodiment, it means that there is no concentration gradient of aluminum from the center to the surface in the core particle, or the aluminum concentration of the inner part of the core particle is neither higher than nor lower than the aluminum concentration of the outer part, and the aluminum is uniformly distributed in the core particle. The aforementioned may be a structure obtained by using an aluminum raw material (hereinafter, also referred to as "Al raw material") during precursor production, and not additionally doping aluminum during the synthesis of the core particle, thereby using a nickel-manganese-aluminum composite hydroxide as a precursor to synthesize a lithium-nickel-manganese-aluminum composite oxide. The core particle may be in the form of a secondary particle in which a plurality of primary particles are aggregated, and the aluminum content inside the primary particle may be the same or similar, regardless of the position of the primary particle. In an embodiment, if a primary particle is selected at a random position in the cross section of the secondary particle, and the aluminum content is measured inside the primary particle rather than at its interface, then regardless of the position of the primary particle (e.g., regardless of whether the primary particle is close to the center of the secondary particle or close to its surface), the aluminum content may be the same / similar / uniform. In an embodiment of this structure, even if cobalt is absent or present in a very small amount, a stable layered structure can be maintained and aluminum byproducts and / or aluminum aggregates are not generated, thereby simultaneously improving the capacity, efficiency and cycle life characteristics of the positive electrode active material.

[0044] The lithium nickel manganese-based composite oxide may be represented by Chemical Formula 1.

[0045] [Chemical formula 1]

[0046] Li a1 Ni x1 Mn y1 Al z1 M 1 w1 O 2-b1 X b1

[0047] In Chemical Formula 1, 0.9≤a1≤1.8, 0.6≤x1≤0.8, 0.1≤y1≤0.4, 0≤z1≤0.03, 0≤w1≤0.3, 0.9≤x1+y1+z1+w1≤1.1, and 0≤b1≤0.1, M 1 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y and Zr, and X is one or more elements selected from F, P and S.

[0048] In an embodiment, in Chemical Formula 1, 0.9 ≤ a1 ≤ 1.5, or 0.9 ≤ a1 ≤ 1.2. In an embodiment, Chemical Formula 1 may contain aluminum and may satisfy 0.6 ≤ x1 ≤ 0.8, 0.1 ≤ y1 ≤ 0.39, 0.01 ≤ z1 ≤ 0.03, and 0 ≤ w1 ≤ 0.29, and may satisfy, for example, 0.6 ≤ x1 ≤ 0.8, 0.1 ≤ y1 ≤ 0.39, 0.01 < z1 ≤ 0.03, and 0 ≤ w1 ≤ 0.29.

[0049] In an embodiment, in Chemical Formula 1, for example, 0.6 ≤ x1 ≤ 0.79, 0.6 ≤ x1 ≤ 0.78, 0.6 ≤ x1 ≤ 0.75, 0.65 ≤ x1 ≤ 0.8, or 0.7 ≤ x1 ≤ 0.79; 0.1 ≤ y1 ≤ 0.35, 0.1 ≤ y1 ≤ 0.30, 0.1 ≤ y1 ≤ 0.29, 0.15 ≤ y1 ≤ 0.39, or 0.2 ≤ y1 ≤ 0.3; 0.01 ≤ z1 ≤ 0.025, 0.01 < z1 ≤ 0.02, or 0.01 < z1 ≤ 0.019; and 0 ≤ w1 ≤ 0.28, 0 ≤ w1 ≤ 0.27, 0 ≤ w1 ≤ 0.26, 0 ≤ w1 ≤ 0.25, 0 ≤ w1 ≤ 0.24, 0 ≤ w1 ≤ 0.23, 0 ≤ w1 ≤ 0.22, 0 ≤ w1 ≤ 0.21, 0 ≤ w1 ≤ 0.2, 0 ≤ w1 ≤ 0.15, 0 ≤ w1 ≤ 0.1, or 0 ≤ w1 ≤ 0.09.

[0050] The lithium nickel manganese composite oxide may be a cobalt-free compound that does not include cobalt or includes a very small amount of cobalt. For example, based on 100 mol% of the total metals other than lithium in the lithium nickel manganese composite oxide, the cobalt content of the lithium nickel manganese composite oxide may be about 0 mol% to about 0.01 mol%.

[0051] The core particles may be in the form of secondary particles formed by aggregating a plurality of primary particles. The secondary particles may be spherical, elliptical, polyhedral, and / or irregular in shape, and the primary particles may be spherical, elliptical, plate-like, or a combination thereof.

[0052] If the battery is operated under high voltage and / or high temperature conditions, the core particles are vulnerable to chemical attack by the components in the electrolyte, and side reactions with the electrolyte may occur. In these cases, there are problems of reducing the battery cycle life and safety due to the generation of a large amount of gas. According to some embodiments to be further described below, these problems can be solved by introducing a coating.

[0053] The first positive electrode active material

[0054] Based on 100 mol% of the total metal other than lithium in the positive electrode active material, the Al content in the first coating layer may be about 0.1 mol% to about 2 mol%, such as about 0.2 mol% to about 1.9 mol%, about 0.3 mol% to about 1.8 mol%, about 0.5 mol% to about 1.5 mol% or about 0.8 mol% to about 1.3 mol%. The foregoing refers only to the content of aluminum included in the first coating layer, which is separate from the aluminum included in the core particles. The aluminum content in the first coating layer can be measured, for example, by scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDS) analysis of the surface and / or cross-section of the positive electrode active material. If the aluminum content in the first coating layer satisfies the above range, the coating layer can have a uniform (or substantially uniform) and thin thickness, which does not increase the impedance of the positive electrode active material, and effectively inhibits or reduces side reactions with the electrolyte, thereby improving the cycle life characteristics of the rechargeable lithium battery under high voltage and high temperature conditions. For example, if the aluminum content of the first coating layer is too much, a uniform coating layer may not be formed and / or impedance (e.g., resistance) may increase, which may reduce charge / discharge efficiency and cycle life characteristics, and if the aluminum content of the first coating layer is too little, a coating layer of appropriate or suitable thickness may not be formed and the effect of inhibiting or reducing side reactions with the electrolyte may be reduced.

[0055] The first coating may be in the form of a film that is continuous (or substantially continuous) around the surface of the core particle, for example, it may be in the form of a shell that surrounds the entire surface of the core particle. This is different from a structure in which only a portion of the surface of the core particle is partially coated. According to some embodiments, the first coating may be formed to completely cover the surface of the core particle, and may be formed to be very thin and uniform (or substantially uniform) in thickness, so that the positive electrode active material does not increase impedance (e.g., resistance) or reduce capacity, improve structural stability, effectively inhibit or reduce side reactions with the electrolyte, reduce the amount of gas generated under high voltage and high temperature conditions, and achieve long cycle life characteristics.

[0056] The thickness of the coating may be about 5 nm to about 40 nm, for example, about 5 nm to about 30 nm or about 5 nm to about 20 nm. If the coating satisfies the above thickness range, the structural stability of the positive electrode active material can be improved without increasing impedance (e.g., resistance) or reducing capacity due to the coating, and the side reaction with the electrolyte can be effectively suppressed or reduced. The thickness of the coating can be measured by, for example, scanning electron microscopy (SEM), transmission electron microscopy (TEM), time-of-flight-secondary ion mass spectrometry (TOF-SIMS), X-ray photoelectron spectroscopy (XPS) and / or energy dispersive X-ray spectroscopy (EDS) analysis, and the thickness range of the coating can be measured by TEM-EDS line profile.

[0057] The first coating may be thicker than the second coating described further below.

[0058] The first coating layer may be thin and uniform (or substantially uniform) in thickness, at the level of a few nanometers to tens of nanometers. For example, the deviation of the coating thickness in a positive electrode active material particle may be less than or equal to about 20%, less than or equal to about 18%, or less than or equal to about 15%. In this article, the deviation of the coating thickness refers to the deviation of the coating thickness in a positive electrode active material particle. For example, the deviation of the coating thickness can be calculated by measuring the thickness of about 10 points in the electron microscope image of the cross section of a single positive electrode active material particle to calculate the arithmetic mean, and then the absolute value of the difference between a measured data and the arithmetic mean is divided by the arithmetic mean and multiplied by 100. The fact that the deviation or standard deviation of the first coating thickness meets the above range means that a coating layer of uniform (or substantially uniform) thickness is well formed on the surface of the core particle of the positive electrode active material in the form of a film. Accordingly, the structural stability of the positive electrode active material is improved, the side reaction with the electrolyte is effectively suppressed or reduced, and the increase in impedance or the decrease in capacity caused by the coating can be minimized or reduced.

[0059] The first coating layer may include, for example, aluminum oxide, lithium aluminum oxide, or a combination thereof. The first coating layer may have a layered structure. In an embodiment, the compound included in the first coating layer may have a layered structure.

[0060] In addition to aluminum, the first coating may further contain nickel, manganese, or a combination thereof.

[0061] Second coating

[0062] Based on 100 mol% of the total metal other than lithium in the positive electrode active material, the Co content in the second coating layer may be about 0.01 mol% to about 1 mol%, such as about 0.01 mol% to about 0.9 mol%, about 0.01 mol% to about 0.7 mol%, about 0.05 mol% to about 0.5 mol%, or about 0.1 mol% to about 0.4 mol%. The Co content in the second coating layer may be measured, for example, by SEM-EDS analysis of the surface or cross section of the positive electrode active material. If the Co content in the second coating layer satisfies the above range, the coating layer may have a uniform (or substantially uniform) and thin thickness, which does not increase the impedance (e.g., resistance) of the positive electrode active material, and effectively inhibits or reduces side reactions with the electrolyte, thereby improving the cycle life characteristics of the rechargeable lithium battery under high voltage and high temperature conditions. For example, if the Co content of the second coating layer is too much, a uniform coating layer may not be formed or impedance (e.g., resistance) may increase, which may reduce charge / discharge efficiency and cycle life characteristics, and if the Co content of the second coating layer is too little, a coating layer of appropriate or suitable thickness may not be formed, and the effect of suppressing or reducing side reactions with the electrolyte may be reduced.

[0063] The second coating layer may be in the form of a film or shell that is continuous (or substantially continuous) around the surface of the first coating layer. According to some embodiments, because the coating layer is formed to completely surround the outermost surface of the positive electrode active material, but still has a very thin and uniform (or substantially uniform) thickness, the positive electrode active material may neither show an increase in impedance (e.g., resistance) nor deteriorate capacity, but improve structural stability, effectively inhibit or reduce side reactions with the electrolyte, reduce gas generation, and achieve long-term cycle life characteristics.

[0064] The thickness of the second coating layer may be less than or equal to about 10 nm, for example, about 0.1 nm to about 10 nm, about 0.5 nm to about 9 nm, about 1 nm to about 7 nm, or about 1 nm to about 5 nm. If the thickness of the second coating layer satisfies the above range, the structural stability of the positive electrode active material can be improved without increasing the impedance (e.g., resistance) or reducing the capacity due to the coating layer, and the side reaction with the electrolyte can be effectively suppressed or reduced. The thickness of the coating layer can be measured by, for example, SEM, TEM, TOF-SIMS, XPS and / or EDS analysis, and the thickness range of the coating layer can be measured by TEM-EDS line profile.

[0065] According to some embodiments, the second coating layer may be thin and uniform (or substantially uniform) in thickness, at the level of several nanometers to tens of nanometers. For example, the variation in the thickness of the second coating layer within a positive electrode active material particle may be less than or equal to about 20%, less than or equal to about 18%, or less than or equal to about 15%. In this article, the deviation of the coating thickness refers to the deviation of the coating thickness within a positive electrode active material particle. For example, the deviation of the coating thickness can be calculated by measuring the thickness of about 10 points in the electron microscope image of the cross section of a single positive electrode active material particle to calculate the arithmetic mean, and then the absolute value of the difference between one measurement data and the arithmetic mean is divided by the arithmetic mean and multiplied by 100. The fact that the deviation or standard deviation of the second coating thickness meets the above range means that a coating layer of uniform (or substantially uniform) thickness is well formed in the form of a film on the surface of the core particle of the positive electrode active material. Accordingly, the structural stability of the positive electrode active material is improved, the side reaction with the electrolyte is effectively suppressed or reduced, and the increase in impedance (e.g., resistance) or the decrease in capacity due to the coating can be minimized or reduced.

[0066] In addition to Co, the second coating may further include Al. The second coating may include, for example, cobalt oxide, lithium cobalt oxide, aluminum cobalt oxide, lithium aluminum cobalt oxide, or a combination thereof. The second coating may have a layered structure. The core, the first coating, and the second coating all have a layered crystal structure, which can further promote the insertion and deinsertion of lithium.

[0067] In an embodiment, the first coating layer may be thicker than the second coating layer. For example, the ratio of the thickness of the second coating layer to the thickness of the first coating layer may be less than or equal to about 0.5, for example, less than or equal to about 0.4 or less than or equal to about 0.3. If the thickness of the first coating layer and the thickness of the second coating layer satisfy the above relationship, the structural stability of the positive electrode active material can be improved without increasing impedance (e.g., resistance) or reducing capacity due to the coating layer; and high voltage characteristics and high temperature characteristics can be improved by effectively suppressing or reducing side reactions with the electrolyte.

[0068] The Al content of the first coating layer may be greater than the Co content of the second coating layer. In this article, the content may mean the molar content or the molar content of the total metal other than lithium relative to 100 mol% in the positive electrode active material. For example, the ratio of the Co content of the second coating layer to the Al content of the first coating layer may be less than 0.5, for example, less than or equal to about 0.4 or less than or equal to about 0.3. If the Al content of the first coating layer and the Co content of the second coating layer satisfy the above relationship, the structural stability of the positive electrode active material can be improved without increasing impedance (e.g., resistance) or reducing capacity due to the coating layer; and the high voltage characteristics and high temperature characteristics can be improved by effectively suppressing or reducing side reactions with the electrolyte.

[0069] Grain boundary coating part

[0070] In an embodiment, during the first coating formation process, aluminum may diffuse into the core particles. Accordingly, the positive electrode active material according to some embodiments may further include a grain boundary coating portion, which includes aluminum on the surface of the primary particles in the internal portion of the secondary particles. In this article, the secondary particle refers to the core particle, and the internal portion of the secondary particle may mean the entire internal portion except the surface of the secondary particle, or may be a zone of about 60% of the radius of the secondary particle (i.e., the distance from the surface of the secondary particle to the center of the secondary particle) from the center of the secondary particle to the surface of the secondary particle. The grain boundary coating is a different concept from the coating on the surface of the core particle, and refers to the coating portion formed on the surface of the primary particle inside the core particle. The presence of the grain boundary coating portion can be confirmed by SEM-EDS analysis of the cross section of the positive electrode active material. By forming an aluminum grain boundary coating portion, the positive electrode active material can become more structurally stable, and its cycle life characteristics can be improved.

[0071] The aluminum content in the grain boundary coating portion is not particularly limited, and for example, the aluminum content in the grain boundary coating portion may be smaller than the aluminum content in the first coating layer.

[0072] In an embodiment, the grain boundary coating portion may further include nickel, magnesium, yttrium, or a combination thereof in addition to aluminum.

[0073] According to some embodiments, the average particle size (D 50 ) is not particularly limited, but may be, for example, about 1 μm to about 25 μm, about 5 μm to about 20 μm, about 10 μm to about 20 μm, about 11 μm to about 18 μm, or about 12 μm to about 15 μm. As used herein, if no limitation is otherwise provided, the average particle size (D 50 ) means the diameter of particles with a cumulative volume of 50% by volume in a particle size distribution obtained by randomly measuring the size (diameter or major axis length) of about 20 particles in a scanning electron microscope image of the positive electrode active material. If the average particle size of the positive electrode active material satisfies the above range, high capacity and long cycle life can be achieved, and it can form a coating according to some embodiments.

[0074] The cobalt content in the positive electrode active material according to some embodiments may be, for example, less than or equal to about 0.01 mol%, less than or equal to about 0.005 mol%, or less than or equal to about 0.001 mol%, for example, about 0 mol% to about 0.01 mol%, based on 100 mol% of the total metals other than lithium in the positive electrode active material. The positive electrode active material according to some embodiments may be, for example, a cobalt-free positive electrode active material (e.g., a positive electrode active material that does not contain cobalt at all).

[0075] In some embodiments, another positive electrode active material may not include sodium. In an embodiment, the other positive electrode active material may be substantially free of sodium (if any, only as an incidental impurity), so that sodium is present in the other positive electrode active material. In an embodiment, the other positive electrode active material may be completely free of sodium. Sodium ions can be used in the preparation process of the positive electrode active material, but according to the preparation method further described below, a core particle having a stable structure and a coating of uniform (or substantially uniform) thickness can be formed without the use of sodium ions.

[0076] Method for preparing positive electrode active material

[0077] In some embodiments, the method for preparing a positive electrode active material includes: mixing a nickel manganese composite hydroxide and a lithium raw material together, and performing a first heat treatment to obtain a lithium nickel manganese composite oxide; adding an Al raw material and a lithium nickel manganese composite oxide to an aqueous solvent, followed by mixing, and adding a Co raw material, followed by mixing; and drying them and performing a second heat treatment. The aforementioned positive electrode active material can be prepared by this method.

[0078] The layered nickel-manganese composite hydroxide (i.e., nickel-manganese composite hydroxide) as the core particle precursor may be in the form of secondary particles in which a plurality of primary particles are aggregated, may not contain cobalt or may contain a very small amount of cobalt, for example, may be a cobalt-free nickel-manganese composite hydroxide. The nickel-manganese-aluminum composite hydroxide may be prepared by a general coprecipitation method.

[0079] Based on 100mol% of the total metal in the nickel-manganese composite hydroxide, the nickel content in the nickel-manganese composite hydroxide may be greater than or equal to about 60mol%, for example, about 60mol% to about 80mol%, about 65mol% to about 80mol%, about 70mol% to about 80mol%, about 60mol% to about 79mol%, about 60mol% to about 78mol% or about 60mol% to about 75mol%. If the nickel content meets the above range, even if the cobalt content is reduced, high capacity can be achieved and structural stability can be increased.

[0080] The manganese content in the layered nickel-manganese composite hydroxide may be greater than or equal to about 10 mol%, for example, about 10 mol% to about 40 mol%, about 15 mol% to about 39 mol%, about 15 mol% to about 35 mol%, about 15 mol% to about 30 mol%, or about 20 mol% to about 30 mol%, etc., based on 100 mol% of total metals in the layered nickel-manganese composite hydroxide.

[0081] In an embodiment, if the nickel-manganese composite hydroxide further contains aluminum, the aluminum content may be greater than 0 mol% and less than or equal to 3 mol%, for example, greater than or equal to about 0.1 mol%, greater than or equal to about 0.5 mol%, or greater than or equal to about 1 mol%, for example, 0 mol% to 3 mol%, about 1 mol% to about 3 mol%, about 1 mol% to about 2.5 mol%, about 1 mol% to about 2 mol%, or about 1 mol% to about 1.9 mol%. If the manganese and aluminum contents of the nickel-manganese composite hydroxide meet the above range, high capacity can be achieved, the structural stability of the positive electrode active material can be increased, and the production price can be reduced to increase economic benefits.

[0082] In the method for preparing a positive electrode active material according to some embodiments, when preparing the core particles, aluminum is not additionally doped, but an aluminum raw material can be used to prepare a precursor, so that a nickel-manganese-aluminum composite hydroxide in which aluminum is uniformly (or substantially uniformly) dispersed in the structure can be used as a precursor. If such a precursor is used, the positive electrode active material can stably maintain a layered structure without cobalt despite repeated charging and discharging, and aluminum byproducts and / or aluminum aggregates may not be formed, improving the capacity and efficiency characteristics and cycle life characteristics of the positive electrode active material.

[0083] In the layered nickel-manganese composite hydroxide, the cobalt content may be less than or equal to about 0.01 mol%, less than or equal to about 0.005 mol%, or less than or equal to about 0.001 mol%, for example, 0 mol% to 0.01 mol%, based on 100 mol% of the total metal in the layered nickel-manganese composite hydroxide. This nickel-manganese composite hydroxide can be economical because it avoids or reduces the increase in unit cost caused by cobalt, maximizes or increases capacity, and improves structural stability.

[0084] As an example, the nickel-manganese-based composite hydroxide may be represented by Chemical Formula 2.

[0085] [Chemical formula 2]

[0086] Ni x2 Mn y2 Al z2 M 2 w2 (OH)2

[0087] In Formula 2, 0.6≤x2≤0.8, 0.1≤y2≤0.4, 0≤z2≤0.03, 0≤w2≤0.3, and 0.9≤x2+y2+z2+w2≤1.1, and M 2 It is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y and Zr.

[0088] In Chemical Formula 2, for example, 0.6≤x2≤0.8, 0.1≤y2≤0.39, 0.01≤z2≤0.03, and 0≤w2≤0.29.

[0089] The layered nickel-manganese composite hydroxide is in the form of particles, and the average particle size (D 50 ) may be about 1 μm to about 25 μm, about 5 μm to about 20 μm, about 10 μm to about 20 μm, about 11 μm to about 18 μm, or about 12 μm to about 15 μm.

[0090] The nickel-manganese composite hydroxide and the lithium raw material can be mixed in a molar ratio of about 1:0.9 to about 1:1.8, for example, about 1:0.9 to about 1:1.5 or about 1:0.9 to about 1:1.2. The first heat treatment can be carried out in an oxygen atmosphere, for example, in a temperature range of about 750°C to about 950°C, about 780°C to about 900°C, or about 810°C to about 890°C for about 2 hours to about 20 hours or about 4 hours to about 12 hours. By heat treatment, a lithium nickel-manganese composite oxide can be obtained. The obtained lithium nickel-manganese composite oxide is substantially the same as the lithium nickel-manganese composite oxide described for the core particles in the positive electrode active material section.

[0091] The lithium nickel manganese composite oxide has a significantly different residual lithium content and different surface characteristics from an oxide having other compositions (e.g., another nickel oxide, such as a lithium nickel cobalt manganese composite oxide, a lithium nickel cobalt aluminum composite oxide, etc.), and the existing coating method may not be able to successfully form a good coating in the form of a uniform (or substantially uniform) film thereon. In some embodiments, such a method (by uniformly (or substantially uniformly) forming a very thin coating on the surface of a layered lithium nickel manganese composite oxide including a very small amount of cobalt and a nickel content greater than or equal to about 60 mol%) is applied to improve high voltage characteristics.

[0092] In some embodiments, the Al raw material is added to an aqueous solvent and mixed together, and then a layered lithium nickel manganese composite oxide is added and mixed together to introduce a first coating on the surface of the layered lithium nickel manganese composite oxide particles (core particles). Subsequently, the Co raw material is added to the mixed solution and mixed together to introduce a second coating. After removing the solvent from the mixed solution and drying, a second heat treatment is performed to obtain a positive electrode active material in which a first coating containing Al and a second coating containing Co are sequentially formed on the surface of the core particles. This can be referred to as a continuous wet coating method.

[0093] The aqueous solvent may include distilled water, an alcohol solvent or a combination thereof. The Al raw material may include, for example, aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum hydroxide or a combination thereof. For example, the Al raw material may include aluminum sulfate, and in this case, it is beneficial to form a first coating having a uniform (or substantially uniform) thickness on the surface of the lithium nickel manganese composite oxide particles.

[0094] Based on 100 mol% of the total metals other than lithium in the positive electrode active material, the Al content in the aluminum raw material can be designed to be about 0.1 mol% to about 2 mol%, such as about 0.2 mol% to about 1.9 mol%, about 0.3 mol% to about 1.8 mol%, about 0.5 mol% to about 1.5 mol%, or about 0.8 mol% to about 1.3 mol%. If the Al content in the first coating layer is designed to have the above range, the first coating layer can be formed to have a thin and uniform (or substantially uniform) thickness of several nanometers to tens of nanometers, which can reduce the amount of gas generated by the rechargeable lithium battery under high voltage and / or high temperature operating conditions, and improve high capacity and long cycle life characteristics.

[0095] The solution obtained by mixing the aluminum raw materials together in an aqueous solvent may have a pH of about 1.5 to about 3.5, for example, about 2.0 to about 3.4, about 2.5 to about 3.3, about 2.7 to about 3.3, or about 2.9 to about 3.2. The lithium nickel manganese composite oxide is added dropwise and mixed into the aqueous solvent mixed with the aluminum raw materials for about 5 minutes to about 80 minutes, about 5 minutes to about 60 minutes, or about 5 minutes to about 40 minutes. After stirring, the mixed solution may have a pH of about 4.5 to about 8.5, for example, about 5.0 to about 8.0, about 5.5 to about 7.5, or about 6.0 to about 7.0. If the above conditions are met, it is beneficial to form a first coating layer with a uniform (or substantially uniform) thickness.

[0096] The Co raw material may include, for example, cobalt nitrate, cobalt sulfate, cobalt carbonate, cobalt hydroxide, or a combination thereof. Based on 100 mol% of the total metal other than lithium in the positive electrode active material, the Co content of the Co raw material may be designed to be about 0.01 mol% to about 1 mol%, such as about 0.01 mol% to about 0.9 mol%, about 0.01 mol% to about 0.7 mol%, about 0.05 mol% to about 0.5 mol%, or about 0.1 mol% to about 0.4 mol%. If the Co content in the second coating is designed to have the above range, the second coating may be formed to have a thin and uniform (or substantially uniform) thickness of several nanometers to tens of nanometers, which may improve the performance of the rechargeable lithium battery under high voltage or high temperature operating conditions, as well as high capacity and long cycle life characteristics.

[0097] The addition and mixing of the Co raw material may be performed for about 5 minutes to about 80 minutes, about 5 minutes to about 60 minutes, or about 10 minutes to about 40 minutes. After stirring, the mixed solution may have a pH of about 4.5 to about 8.5, such as about 5.0 to about 8.0, about 5.5 to about 7.5, or about 6.0 to about 7.0. If these conditions are met, it is beneficial to form a second coating layer having a uniform (or substantially uniform) thickness.

[0098] Removal of the solvent and drying of the residue may be performed, for example, at about 40°C to about 240°C, about 100°C to about 220°C, or about 150°C to about 200°C.

[0099] The second heat treatment may be performed, for example, in an oxygen atmosphere at a temperature range of about 700°C to about 850°C, about 750°C to about 840°C, or about 800°C to about 830°C for about 2 hours to about 20 hours or about 3 hours to about 10 hours. In an embodiment, the second heat treatment temperature may be lower than the first heat treatment temperature, and the second heat treatment time may be the same as the first heat treatment time or shorter than the first heat treatment time. An appropriate or desired coating may be obtained by performing a second heat treatment under these conditions.

[0100] Positive electrode

[0101] In some embodiments, the positive electrode includes a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector, wherein the positive electrode active material layer includes the positive electrode active material described above. In addition to the positive electrode active material described above, the positive electrode active material layer may further include other types (or types) of positive electrode active materials. In an embodiment, the positive electrode active material layer may optionally further include a binder, a conductive material (e.g., a conductive material) or a combination thereof.

[0102] According to some embodiments, the loading level of the positive electrode active material layer may be about 10 mg / cm 2 ~ about 40mg / cm 2 , for example about 10 mg / cm 2 ~about 30mg / cm 2 or about 10 mg / cm 2 ~about 20mg / cm 2 . In an embodiment, the density of the positive electrode active material layer in the final pressed positive electrode may be about 3.3 g / cc to about 3.7 g / cc, for example, about 3.3 g / cc to about 3.6 g / cc or about 3.4 g / cc to about 3.58 g / cc. If the positive electrode active material according to some embodiments is applied, it is advantageous to implement such a loading level and density of the positive electrode active material layer, and the positive electrode in which the loading level and density of the positive electrode active material layer meet the above range is suitable for implementing a high-capacity, high-energy-density rechargeable lithium battery.

[0103] Binder

[0104] The binder improves the bonding properties between the positive electrode active material particles and the bonding properties between the positive electrode active material particles and the positive electrode current collector. Examples of the binder may include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth) acrylated styrene-butadiene rubber, epoxy resin, (meth) acrylic resin, polyester resin and / or nylon, but are not limited thereto.

[0105] Conductive Materials

[0106] The conductive material is included to provide electrode conductivity (e.g., electrical conductivity), and any suitable conductive material may be used as the conductive material unless it causes chemical changes (e.g., causes undesirable chemical changes in a rechargeable lithium battery). Examples of the conductive material may include: carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube, etc.; metal-based materials including metal powders and / or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymers (e.g., conductive polymers) such as polyphenylene derivatives; or mixtures thereof.

[0107] The binder and the conductive material may each be present in an amount of about 0.5 wt % to about 5 wt % based on 100 wt % of the positive electrode active material layer.

[0108] The positive electrode current collector may include Al foil, but is not limited thereto.

[0109] Rechargeable lithium battery

[0110] Some embodiments provide a rechargeable lithium battery including the aforementioned positive electrode, negative electrode, and electrolyte. As an example, the rechargeable lithium battery may include a positive electrode, a negative electrode, a separator between the positive electrode and the negative electrode, and an electrolyte.

[0111] Rechargeable lithium batteries may be classified into cylindrical batteries, prismatic batteries, pouch batteries, coin batteries, etc., depending on the shape. Figure 1 to Figure 4 is a schematic diagram showing a rechargeable lithium battery according to some embodiments, wherein Figure 1 For cylindrical batteries, Figure 2 is a prismatic cell, and Figure 3-4 Each is a pouch-shaped battery. Figure 1 to Figure 4 , the rechargeable lithium battery 100 includes: an electrode assembly 40 including a separator 30 between a positive electrode 10 and a negative electrode 20, and a case 50 in which the electrode assembly 40 is accommodated. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte solution. Figure 1As shown in FIG, the rechargeable lithium battery 100 may include a sealing member 60 that seals the housing 50. Figure 2 In the embodiment, the rechargeable lithium battery 100 may include a positive electrode lead tab 11, a positive electrode terminal 12, a negative electrode lead tab 21, and a negative electrode terminal 22. Figure 3-4 As shown in FIG. 1 , the rechargeable lithium battery 100 includes an electrode tab 70 ( Figure 4 ), for example, the positive electrode terminal tab 71 and the negative electrode terminal tab 72 ( Figure 3 ), which serves as an electrical path for introducing the current generated in the electrode assembly 40 to the outside.

[0112] The rechargeable lithium battery according to some embodiments may be rechargeable at a high voltage, or may be suitable for being driven at a high voltage. For example, the charging voltage of the rechargeable lithium battery may be greater than or equal to about 4.45V, about 4.45V to about 4.7V, about 4.45V to about 4.6V, or about 4.45V to about 4.55V. By applying the positive electrode active material according to some embodiments, the rechargeable lithium battery can significantly reduce the amount of gas generated even when charged at a high voltage, and can achieve high capacity and long cycle life characteristics.

[0113] Negative electrode

[0114] The negative electrode may include a negative electrode current collector and a negative electrode active material layer on the negative electrode current collector, and may further include a negative electrode active material, a binder, a conductive material (eg, an electrically conductive material), or a combination thereof.

[0115] Negative electrode active material

[0116] The negative electrode active material may include a material that reversibly intercalates / deintercalates lithium ions, lithium metal, a lithium metal alloy, a material capable of doping / dedoping lithium, and / or a transition metal oxide.

[0117] The material that can reversibly intercalate / deintercalate lithium ions may include, for example, crystalline carbon, amorphous carbon, or a combination thereof as a carbonaceous negative electrode active material. Crystalline carbon may be amorphous and / or flaky, flake-like, spherical, and / or fibrous natural graphite and / or artificial graphite. Amorphous carbon may be soft carbon, hard carbon, mesophase pitch carbonization product, calcined coke, etc.

[0118] Lithium metal alloys include alloys of lithium and a metal selected from the group consisting of Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn.

[0119] The material capable of being doped / undoped with lithium may be a Si-based negative electrode active material and / or a Sn-based negative electrode active material. The Si-based negative electrode active material may include silicon, a silicon-carbon composite, SiO x(0 < x ≤ 2), Si-Q alloy (where Q is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements (excluding Si), Group 15 elements, Group 16 elements, transition metals, rare earth elements, and combinations thereof, such as Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof) or a combination thereof. The Sn-based negative electrode active material can be Sn, SnO2, Sn alloy, SnO x (0 < x < 2) or a combination thereof.

[0120] The silicon-carbon composite can be a composite of silicon and amorphous carbon. The average particle size (D 50 ) can be, for example, about 0.5 μm to about 20 μm. According to some embodiments, the silicon-carbon composite can be in the form of silicon particles and amorphous carbon coated on the surface of the silicon particles. For example, it can include secondary particles (cores) in which silicon primary particles are aggregated and an amorphous carbon coating (shell) on the surface of the secondary particles. Amorphous carbon can also be present between the silicon primary particles. For example, the silicon primary particles can be coated with amorphous carbon. The secondary particles can be dispersed in an amorphous carbon matrix.

[0121] The silicon-carbon composite can further include crystalline carbon. For example, the silicon-carbon composite can include: a core including crystalline carbon and silicon particles and an amorphous carbon coating on the surface of the core. The crystalline carbon can be artificial graphite, natural graphite, or a combination thereof. The amorphous carbon can include soft carbon, hard carbon, mesophase pitch carbonization products, and / or calcined coke.

[0122] If the silicon-carbon composite includes silicon and amorphous carbon, based on 100 wt% of the silicon-carbon composite, the content of silicon can be about 10 wt% to about 50 wt% and the content of amorphous carbon can be about 50 wt% to about 90 wt%. In an embodiment, if the silicon-carbon composite includes silicon, amorphous carbon, and crystalline carbon, based on 100 wt% of the silicon-carbon composite, the content of silicon can be about 10 wt% to about 50 wt%, the content of crystalline carbon can be about 10 wt% to about 70 wt%, and the content of amorphous carbon can be about 20 wt% to about 40 wt%.

[0123] In an embodiment, the thickness of the amorphous carbon coating can be about 5 nm to about 100 nm. The average particle size (D 50) can be from about 10 nm to about 1 μm or from about 10 nm to about 200 nm. The silicon particles can exist as silicon alone, in the form of a silicon alloy, or in the oxidized form of silicon. The oxidized form of silicon can be represented by SiO x (0 < x ≤ 2). At this time, the atomic content ratio of Si:O indicating the degree of oxidation can be from about 99:1 to about 33:67. As used herein, if no other definition is provided, the average particle size (D 50 ) indicates the diameter of the particles with a cumulative volume of about 50% by volume in the particle size distribution.

[0124] Si-based negative electrode active materials and / or Sn-based negative electrode active materials can be mixed with carbon-based negative electrode active materials. If Si-based negative electrode active materials and / or Sn-based negative electrode active materials are mixed with carbon-based negative electrode active materials and used, the mixing ratio can be a weight ratio of from about 1:99 to about 90:10.

[0125] Binder

[0126] The binder is used to bond the negative electrode active material particles well to each other and is also used to bond the negative electrode active material to the negative electrode current collector. The binder can be a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof.

[0127] The non-aqueous binder can include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene-propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or a combination thereof.

[0128] The aqueous binder can include styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinylpyrrolidone, epichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene-propylene-diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, or a combination thereof.

[0129] If the aqueous binder is used as the binder in the negative electrode active material layer, a cellulose-based compound capable of imparting or increasing viscosity can be further included. As the cellulose-based compound, one or more selected from carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, and their alkali metal salts can be mixed and used. The alkali metal can be Na, K, and / or Li.

[0130] The dry binder may be a polymer material that can become a fiber (eg, can be fiberized or fibrillated), and may be, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or a combination thereof.

[0131] Conductive Materials

[0132] The conductive material is included to provide electrode conductivity (e.g., electrical conductivity), and any suitable conductive material may be used as the conductive material unless it causes chemical changes (e.g., causes undesirable chemical changes in a rechargeable lithium battery). Examples of the conductive material include: carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube, etc.; metal-based materials including metal powders and / or metal fibers of copper, nickel, aluminum silver, etc.; conductive polymers (e.g., conductive polymers) such as polyphenylene derivatives; or mixtures thereof.

[0133] Based on 100wt% of the negative electrode active material layer, the content of the negative electrode active material may be about 95wt% to about 99.5wt%, and based on 100wt% of the negative electrode active material layer, the content of the binder may be about 0.5wt% to about 5wt%. For example, the negative electrode active material layer may include about 90wt% to about 99wt% of the negative electrode active material, about 0.5wt% to about 5wt% of the binder, and about 0wt% to about 5wt% of the conductive material.

[0134] Negative electrode current collector

[0135] The negative electrode current collector may include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li) and / or alloys thereof, and may be in the form of foil, sheet and / or foam. The thickness of the negative electrode current collector may be, for example, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 7 μm to about 10 μm.

[0136] Electrolytes

[0137] For example, the electrolyte for a rechargeable lithium battery may be an electrolyte that may include a non-aqueous organic solvent and a lithium salt.

[0138] The non-aqueous organic solvent is used as a medium for transmitting ions participating in the electrochemical reaction of the battery. The non-aqueous organic solvent may include a carbonate solvent, an ester solvent, an ether solvent, a ketone solvent, an alcohol solvent, an aprotic solvent, or a combination thereof.

[0139] Carbonate solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. Ester solvents may include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanoic acid lactone, mevalonate lactone, valerolactone, caprolactone, etc. Ether solvents may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc. In an embodiment, ketone solvents may include cyclohexanone, etc. Alcohol solvents may include ethanol, isopropanol, etc., and / or aprotic solvents may include nitriles such as R-CN (wherein R is a C2-C20 straight chain, branched or cyclic hydrocarbon group, and may include double bonds, aromatic rings and / or ether bonds, etc.); amides (such as dimethylformamide); dioxolanes (such as 1,3-dioxolane, 1,4-dioxolane, etc.); cyclopentane sulfones, etc.

[0140] The non-aqueous organic solvent may be used alone or as a mixture of two or more types (or species), and if two or more types (or species) are used in the form of a mixture, the mixing ratio may be appropriately or suitably adjusted according to the appropriate or desired battery performance, and may be any appropriate mixing ratio commonly used in the art.

[0141] If a carbonate-based solvent is used, a cyclic carbonate and a chain carbonate may be mixed together and used, and the cyclic carbonate and the chain carbonate may be mixed together in a volume ratio of about 1:1 to about 1:9.

[0142] The non-aqueous organic solvent may further include an aromatic hydrocarbon organic solvent. For example, a carbonate-based solvent and an aromatic hydrocarbon organic solvent may be mixed together in a volume ratio of about 1:1 to about 30:1 and used.

[0143] The electrolyte may further include vinyl ethylene carbonate, vinylene carbonate and / or ethylene carbonate-based compounds to improve the battery cycle life.

[0144] Examples of the ethylene carbonate-based compound may include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and cyanoethylene carbonate.

[0145] The lithium salt dissolved in the organic solvent supplies lithium ions in the battery, ensures the basic operation of the rechargeable lithium battery, and improves the transport of lithium ions between the positive electrode and the negative electrode. Examples of lithium salts may include those selected from LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (wherein x and y are integers of 1 to 20), at least one of lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalato)phosphate (LiDFBOP) and lithium bis(oxalato)borate (LiBOB).

[0146] The concentration of the lithium salt may be in the range of about 0.1 M to about 2.0 M. If the concentration of the lithium salt is within the above range, the electrolyte may have appropriate or suitable ion conductivity and viscosity, and thus excellent performance may be achieved, and lithium ions may be efficiently moved.

[0147] Diaphragm

[0148] Depending on the type (or kind) of the rechargeable lithium battery, the separator may be present between the positive electrode and the negative electrode. The separator may include a polyethylene separator, a polypropylene separator, a polyvinylidene fluoride separator, or a multilayer film of two or more layers thereof (such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, a polypropylene / polyethylene / polypropylene three-layer separator, etc.).

[0149] The separator may include a porous substrate and a coating on one or both surfaces (eg, two opposite surfaces) of the porous substrate, the coating including an organic material, an inorganic material, or a combination thereof.

[0150] The porous substrate may be a polymer film formed from any one of the following polymers or a copolymer or mixture of two or more thereof: polyolefins (such as polyethylene and / or polypropylene), polyesters (such as polyethylene terephthalate and / or polybutylene terephthalate), polyacetals, polyamides, polyimides, polycarbonates, polyether ketones, polyaryletherketones, polyetherimides, polyamideimides, polybenzimidazoles, polyethersulfones, polyphenylene oxides, cyclic olefin copolymers, polyphenylene sulfide, polyethylene naphthalate, glass fibers and / or polytetrafluoroethylene (e.g., Teflon).

[0151] The porous substrate may have a thickness of about 1 μm to about 40 μm, for example, about 1 μm to about 30 μm, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 10 μm to about 15 μm.

[0152] The organic material may include a (meth)acryl-based copolymer, which includes: a first structural unit derived from (meth)acrylamide, and a second structural unit including at least one selected from a structural unit derived from (meth)acrylic acid or (meth)acrylate and a structural unit derived from (meth)acrylamide sulfonic acid or a salt thereof.

[0153] The inorganic material may include inorganic particles selected from the group consisting of Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, and combinations thereof, but is not limited thereto. The average particle size (D 50 ) may be from about 1 nm to about 2000 nm, for example, from about 100 nm to about 1000 nm or from about 100 nm to about 700 nm.

[0154] An organic material and an inorganic material may be mixed together in one coating layer, or a coating layer including an organic material and a coating layer including an inorganic material may be stacked.

[0155] The coating layer may have a thickness of about 0.5 μm to about 20 μm, for example, about 1 μm to about 10 μm or about 1 μm to about 5 μm.

[0156] Examples and comparative examples of the present disclosure are described below. However, the following examples are merely examples of the present disclosure, and the present disclosure is not limited to the following examples.

[0157] Example 1

[0158] 1. Preparation of positive electrode active material

[0159] Ni 0.75 Mn 0.23 Al 0.02 (OH)2 and LiOH were mixed together in a molar ratio of 1:1 and then subjected to a first heat treatment at 850 °C for 8 h in an oxygen atmosphere to prepare LiNi 0.75 Mn 0.23 Al 0.02 O2 composition and an average particle size of about 14 μm (D 50 ) of a lithium nickel manganese composite oxide in the form of secondary particles.

[0160] After aluminum sulfate and distilled water solvent are mixed together, lithium nickel manganese composite oxide is added thereto, and then mixed together for 20 minutes to 60 minutes. In this article, the aluminum content in aluminum sulfate is designed to be 1.0 mol% based on 100 mol% of the total metals other than lithium in the positive electrode active material. Subsequently, cobalt sulfate is added thereto, and then stirred for about 10 minutes to 40 minutes. In this article, the cobalt content of cobalt sulfate is designed to be 0.2 mol% based on 100 mol% of the total metals other than lithium in the final positive electrode active material. After removing the solvent from the mixed solution, the resulting residue is dried at 190 ° C, and a second heat treatment is performed at 825 ° C in an oxygen atmosphere for 8 hours to prepare the final positive electrode active material.

[0161] 2. Preparation of rechargeable lithium battery cells

[0162] Based on the total weight of the positive electrode active material layer slurry, 98.5wt% of the positive electrode active material, 1.0wt% of the polyvinylidene fluoride binder and 0.5wt% of the carbon nanotube conductive material were mixed together to prepare the positive electrode active material layer slurry, and the slurry was coated on an aluminum foil positive electrode current collector, and then dried and pressed to prepare a positive electrode. At this time, the loading level of the positive electrode active material layer was 10mg / cm 2 , and the density of the positive electrode active material layer in the final pressed positive electrode was about 3.4 g / cc.

[0163] Based on the total weight of the negative electrode active material layer slurry, 97.5wt% of graphite negative electrode active material, 1.5wt% of carboxymethyl cellulose and 1wt% of styrene butadiene rubber were mixed together in an aqueous solvent to prepare a negative electrode active material layer slurry. The negative electrode active material layer slurry was coated on a copper foil negative electrode current collector, and then dried and pressed to prepare a negative electrode.

[0164] A rechargeable lithium battery cell was prepared using a polytetrafluoroethylene separator and an electrolyte prepared by dissolving 1M LiPF6 in a mixed solvent of ethylene carbonate and dimethyl carbonate in a volume ratio of 3:7 using a general method.

[0165] Comparative Example 1

[0166] A positive electrode active material and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that the LiNi 0.75 Mn 0.23 Al 0.02 O2 itself is a lithium nickel manganese composite oxide used as the positive electrode active material.

[0167] Comparative Example 2

[0168] A positive electrode active material and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that the positive electrode active material was prepared by dry coating only Al without coating Co.

[0169] The Al dry coating method is carried out as follows. 0.75 Mn 0.23 Al 0.02 A lithium nickel manganese based composite oxide of a composition of 0.147 W / cm2 O2 was mixed with alumina powder, and then the mixture was heat treated at 825°C for 8 hours in an oxygen atmosphere to obtain a positive electrode active material dry-coated with Al.

[0170] Comparative Example 3

[0171] A positive electrode active material and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that the positive electrode active material was prepared by wet coating of Al without coating Co.

[0172] In other words, the positive electrode active material of Comparative Example 3 was prepared by mixing aluminum sulfate in a distilled water solvent, adding a lithium nickel manganese composite oxide thereto, and then stirring the resulting mixture for 20 to 60 minutes, removing the solvent therefrom, drying the residue at 190° C., and subjecting it to a second heat treatment at 825° C. in an oxygen atmosphere for 8 hours.

[0173] Comparative Example 4

[0174] A positive electrode active material and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that the positive electrode active material was prepared by wet coating of Co without coating Al.

[0175] In other words, the positive electrode active material of Comparative Example 4 was prepared by mixing cobalt sulfate in a distilled water solvent, adding a lithium nickel manganese composite oxide thereto, then stirring the mixture for 20 to 40 minutes, removing the solvent therefrom, drying the residue at 190° C., and subjecting it to a second heat treatment at 825° C. in an oxygen atmosphere for 8 hours.

[0176] Evaluation Example 1: Analysis of Positive Electrode Active Material

[0177] The positive electrode active material particles of Example 1 were cut by using a focused ion beam (FIB) to perform SEM-EDS analysis on the cross section thereof. Figure 5 : is a SEM image showing a cross section of the positive electrode active material of Example 1. Figure 6 To highlight by SEM-EDS analysis Figure 5 The image of the Al element in Figure 7 To highlight by SEM-EDS analysis Figure 5Image of the Co element in . Figure 5 to Figure 7 , a first coating layer containing Al was formed to have a uniform thickness on the surface of the secondary particles, and on the first coating layer, a second coating layer containing Co was formed as a thin and uniform film to form an overall uniform double coating layer, which confirmed that a positive electrode active material having a dual core-shell structure was prepared.

[0178] Evaluation Example 2: Charge / discharge characteristics and high temperature cycle life characteristics

[0179] At 25° C., the rechargeable lithium battery cells according to Example 1 and Comparative Examples 1 to 4 were charged to 4.45 V at a constant current of 0.2 C and to 0.05 C at a constant voltage, and then discharged to a cut-off voltage of 3.0 V at 0.2 C as initial charge and discharge, wherein the initial discharge capacity (i.e., 4.45 V initial discharge capacity) was measured.

[0180] Subsequently, at 45°C, the rechargeable lithium battery cell was charged at 1.0C and discharged at 1.0C in a voltage range of 3.0V to 4.45V, repeated 25 times or more, wherein the discharge capacity after the 25th cycle was measured to calculate the ratio of the discharge capacity after the 25th cycle to the initial discharge capacity (i.e., high temperature cycle life), and the results are shown in Table 1.

[0181] Table 1

[0182]

[0183] Referring to Table 1, the rechargeable lithium battery cell of Example 1 exhibits more excellent initial discharge capacity and high temperature cycle-life characteristics than the rechargeable lithium battery cells of Comparative Examples 1 to 4.

[0184] Although the subject matter of the present disclosure has been described in conjunction with example embodiments currently considered to be practical, it should be understood that the present disclosure should not be limited to the disclosed embodiments. Instead, the present disclosure is intended to cover one or more suitable various modifications and equivalent arrangements included within the spirit and scope of the claims and their equivalents.

Claims

1. A positive electrode active material comprising: The core particle includes a layered lithium nickel manganese composite oxide, a first coating layer, on the surface of the core particle and containing Al, and A second coating layer is on the first coating layer and contains Co.

2. The positive electrode active material according to claim 1, wherein: In the layered lithium nickel manganese based composite oxide of the core particle, the nickel content is 60 mol% to 80 mol% and the manganese content is greater than or equal to 10 mol% based on 100 mol% of total metals excluding lithium of the layered lithium nickel manganese based composite oxide.

3. The positive electrode active material according to claim 1, wherein: The layered lithium nickel manganese based composite oxide of the core particle further includes aluminum, and the aluminum content of the core particle is greater than 0 mol % and less than or equal to 3 mol % based on 100 mol % of total metals excluding lithium of the layered lithium nickel manganese based composite oxide.

4. The positive electrode active material according to claim 1, wherein: In the layered lithium nickel manganese-based composite oxide of the core particle, a cobalt content is 0 mol % to 0.01 mol % based on 100 mol % of total metals excluding lithium of the layered lithium nickel manganese-based composite oxide.

5. The positive electrode active material according to claim 1, wherein: The layered lithium nickel manganese-based composite oxide of the core particle is represented by Chemical Formula 1: [Chemical formula 1] Li a1 Ni x1 Mr y1 Al z1 M 1 w1 O 2-b1 X b1 Wherein in Chemical Formula 1, 0.9≤a1≤1.8, 0.6≤x1≤0.8, 0.1≤y1≤0.4, 0≤z1≤0.03, 0≤w1≤0.3, 0.9≤x1+y1+z1+w1≤1.1, and 0≤b1≤0.1, M 1 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y and Zr, and X is one or more elements selected from F, P and S.

6. The positive electrode active material according to claim 1, wherein: The first coating layer and the second coating layer are each in the form of a continuous film.

7. The positive electrode active material according to claim 1, wherein: The thickness of the first coating is 5nm to 40nm, and The thickness of the second coating layer is less than or equal to 10 nm.

8. The positive electrode active material according to claim 1, wherein: A ratio of the thickness of the second coating layer to the thickness of the first coating layer is less than or equal to 0.

5.

9. The positive electrode active material according to claim 1, wherein: The Al content of the first coating layer is 0.1 mol % to 2 mol % based on 100 mol % of the total metals except lithium in the positive electrode active material. The second coating layer may have a Co content of 0.01 mol% to 1 mol% based on 100 mol% of total metals excluding lithium in the positive electrode active material.

10. The positive electrode active material according to claim 1, wherein: The Al content of the first coating layer is 0.5 mol% to 1.5 mol% based on 100 mol% of the total metals except lithium in the positive electrode active material, and The Co content of the second coating layer is 0.05 mol % to 0.5 mol % based on 100 mol % of total metals except lithium in the positive electrode active material.

11. The positive electrode active material according to claim 1, wherein: A ratio of the Co content of the second coating layer to the Al content of the first coating layer is less than 0.

5.

12. The positive electrode active material according to claim 1, wherein: The first coating comprises aluminum oxide, lithium aluminum oxide, or a combination thereof, and The second coating layer includes cobalt oxide, lithium cobalt oxide, aluminum cobalt oxide, lithium aluminum cobalt oxide, or a combination thereof.

13. The positive electrode active material according to claim 1, wherein: The first coating layer and the second coating layer each have a layered structure.

14. The positive electrode active material according to claim 1, wherein: The core particle is in the form of a secondary particle formed by aggregating a plurality of primary particles, and The positive electrode active material includes a grain boundary coating portion containing Al on the surface of the primary particle inside the secondary particle.

15. The positive electrode active material according to claim 14, wherein: The Al content of the grain boundary coating portion is less than the Al content of the first coating layer based on 100 mol % of total metals excluding lithium in the positive electrode active material.

16. The positive electrode active material according to claim 1, wherein: The average particle size D of the positive electrode active material 50 It is 10μm~20μm.

17. A method for preparing a positive electrode active material, comprising: The nickel-manganese composite hydroxide and the lithium raw material are mixed together and subjected to a first heat treatment to obtain a layered lithium-nickel-manganese composite oxide. adding an aluminum raw material to an aqueous solvent, followed by mixing, adding the layered lithium nickel manganese-based composite oxide, followed by mixing, and adding a Co raw material, followed by mixing, and Drying and second heat treatment.

18. The method of claim 17, wherein: In the layered nickel manganese composite hydroxide, based on 100 mol% of total metals of the layered nickel manganese composite hydroxide, the nickel content is 60 mol% to 80 mol%, the manganese content is greater than or equal to 10 mol%, the aluminum content is 0 mol% to 3 mol%, and the cobalt content is 0 mol% to 0.01 mol%.

19. The method of claim 17, wherein: The aluminum raw material has an Al content of 0.1 mol% to 2 mol% based on 100 mol% of total metals excluding lithium in the positive electrode active material, and The Co raw material may have a Co content of 0.01 mol% to 1 mol% based on 100 mol% of total metals excluding lithium in the positive electrode active material.

20. The method of claim 17, wherein: The aluminum raw material includes aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum hydroxide or a combination thereof, and The Co raw material includes cobalt nitrate, cobalt sulfate, cobalt carbonate, cobalt hydroxide or a combination thereof.

21. The method of claim 17, wherein: The solution obtained by mixing the aluminum raw materials together in an aqueous solvent has a pH of 1.5 to 3.

5.

22. The method of claim 17, wherein: The first heat treatment is performed at 750°C to 950°C, and The second heat treatment is performed at 700°C to 850°C.

23. A positive electrode comprising: a positive electrode current collector, and A positive electrode active material layer, on the positive electrode current collector, The positive electrode active material layer comprises the positive electrode active material according to any one of claims 1 to 16 or a positive electrode active material prepared by the method according to any one of claims 17 to 22.

24. The positive electrode of claim 23, wherein: The loading level of the positive electrode active material layer is 10 mg / cm 2 ~40mg / cm 2 .

25. The positive electrode of claim 23, wherein: The positive electrode active material layer has a density of 3.3 g / cc to 3.7 g / cc.

26. A rechargeable lithium battery comprising: The positive electrode according to claim 23, negative electrode, and Electrolytes.

27. The rechargeable lithium battery of claim 26, wherein: The charging voltage of the rechargeable lithium battery is greater than or equal to 4.45V.